The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1210/jc.85.11.4003
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Subcutaneous Pegylated Recombinant Native Human Leptin (PEG-OB) Administration in Obese Men

Abstract: To assess the biological activity and tolerability of pegylated recombinant native human leptin (PEG-OB), 30 obese men (mean body mass index, 33.9 kg/m2) were randomized to a double-blind treatment with weekly sc injections of 20 mg PEG-OB or placebo for 12 weeks, in addition to a hypocaloric diet (deficit, 2 MJ/day). Body composition, energy expenditure, and metabolic parameters were measured before and after treatment. PEG-OB was generally well tolerated based on adverse event reports, lab values, and vital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 0 publications
1
67
1
4
Order By: Relevance
“…However, this is in agreement with other clinical trials demonstrating that leptin is not an effective weight loss agent for obese individuals without congenital leptin deficiency (8,13). Studies reported thus far have seen little change in total fat mass with leptin treatment, which is in agreement with our results (8,14). To our knowledge this is the first trial to examine effects of leptin administration specifically on visceral fat mass.…”
Section: Discussionsupporting
confidence: 93%
“…However, this is in agreement with other clinical trials demonstrating that leptin is not an effective weight loss agent for obese individuals without congenital leptin deficiency (8,13). Studies reported thus far have seen little change in total fat mass with leptin treatment, which is in agreement with our results (8,14). To our knowledge this is the first trial to examine effects of leptin administration specifically on visceral fat mass.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the present findings may offer an explanation for the disappointing results in clinical trials with recombinant human leptin administration, which alone, provides little benefit in obesity treatment. 52 …”
Section: Discussionmentioning
confidence: 99%
“…Serum leptin concentrations were measured according to the method described previously. 33 Attitude towards eating. Attitude towards eating was characterized using a Dutch translation of the TFEQ.…”
Section: Measurementsmentioning
confidence: 99%